Exploring the Bacterial Microbiota of Colombian Fermented Maize Dough “Masa Agria” (Maiz Añejo) - Chaves-Lopez, Clemencia; Serio, Annalisa; Delgado-Ospina, Johannes; Rossi, Chiara; Grande-Tovar, Carlos D.; Paparella, Antonello (Frontiers in Microbiology, 2016)
Masa Agria is a naturally fermented maize dough produced in Colombia, very common in the traditional gastronomy. In this study we used culture-dependent and RNA-based pyrosequencing to investigate the bacterial community structure of Masa Agria samples produced in the south west of Colombia. The mean value of cell density was 7.6 Log CFU/g of presumptive lactic acid bacteria (LAB), 5.4 Log cfu/g for presumptive acetic bacteria and 5.6 Log CFU/g for yeasts. The abundance of these microorganisms is also responsible for the low pH (3.1-3.7) registered. Although the 16S rRNA pyrosequencing revealed that the analyzed samples were different in bacteria richness and diversity, the genera Lactobacillus, Weissella and Acetobacter were predominant. In particular, the most common species were Lactobacillus plantarum and Acetobacter fabarum, followed by Lb. fermentum, Lb. vaccinostercus and Pediococcus argentinicus. Several microorganisms of environmental origin, such as Dechloromonas and most of all Sphingobium spp., revealed in each sample, were detected, and also bacteria related to maize, such as Phytoplasma. In conclusion, our results elucidated for the first time the structures of the bacterial communities of Masa Agria samples obtained from different producers, identifying the specific dominant species and revealing a complete picture of the bacterial consortium in this specific niche. The selective pressure of tropical environments may favour microbial biodiversity characterized by a useful technological potential.